Transcriptomic Responses of Skeletal Muscle to Acute Exercise in Diabetic Goto-Kakizaki Rats - Fu, Shuying; Meng, Yuhuan; Zhang, Wenlu; Wang, Jiajian; He, Yuting; Huang, Lizhen; Chen, Hongmei; Kuang, Jian; Du, Hongli (Frontiers in Physiology, 2019)
Physical activity exerts positive effects on glycemic control in type 2 diabetes (T2D), which is mediated in part by extensive metabolic and molecular remodeling of skeletal muscle in response to exercise, while many regulators of skeletal muscle remain unclear. In the present study, we investigated the effects of acute exercise on skeletal muscle transcriptomic responses in the Goto-Kakizaki (GK) rats which can spontaneously develop T2D. The transcriptomes of skeletal muscle from both 8-week-old GK and Wistar rats that underwent a single exercise session (60 min running using an animal treadmill at 15 m/min) or remained sedentary were analyzed by next-generation RNA sequencing (RNA-Seq). We identified 819 differentially expressed genes (DEGs) in the sedentary GK rats compared with those of the sedentary Wistar rats. After a single bout of running, we found 291 and 598 genes that were differentially expressed in the exercise GK and exercise Wistar rats when compared with the corresponding sedentary rats. By integrating our data and previous studies including RNA or protein expression patterns and transgenic experiments, the downregulated expression of Fasn and upregulated expression of Tbc1d1, Hk2, Lpin1, Ppargc1a, Sorbs1, and Hmox1 might enhance glucose uptake or improve insulin sensitivity to ameliorate hyperglycemia in the exercise GK rats. Our results provide mechanistic insight into the beneficial effects of exercise on hyperglycemia and insulin action in skeletal muscle of diabetic GK rats.